2008
DOI: 10.1371/journal.pone.0003148
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNAs Are Promising Novel Biomarkers

Abstract: BackgroundCirculating nucleic acids (CNAs) offer unique opportunities for early diagnosis of clinical conditions. Here we show that microRNAs, a family of small non-coding regulatory RNAs involved in human development and pathology, are present in bodily fluids and represent new effective biomarkers.Methods and ResultsAfter developing protocols for extracting and quantifying microRNAs in serum and other body fluids, the serum microRNA profiles of several healthy individuals were determined and found to be simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
925
5
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,243 publications
(959 citation statements)
references
References 23 publications
14
925
5
15
Order By: Relevance
“…[27][28][29] Our micro-RNA-based qRT-PCR test has been developed and validated using retrospective FFPE samples with established primary origins. Our technology is highly sensitive and is applicable also to fresh frozen and small samples such as are obtained with fine needle aspirates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[27][28][29] Our micro-RNA-based qRT-PCR test has been developed and validated using retrospective FFPE samples with established primary origins. Our technology is highly sensitive and is applicable also to fresh frozen and small samples such as are obtained with fine needle aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was performed as described, 23,27 using probes for the 104 candidate microRNAs, of which five were tested with two different forward primers, and for U6 snoRNA.…”
Section: Qrt-pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] In addition, reliable methods for extracting miRNAs from bodily fluids, such as serum, have been well developed and well validated. 8,9 Therefore, serum miRNAs could represent novel biomarkers for PCa. 10,11 A study of plasma samples from PCa patients reported that plasma miR-141 levels can be used to screen for metastatic PCa with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%